(untitled) (Journal of Scientific Research, 2012)
Ethylenediaminetetraacetic acid or EDTA was used complementarily with nisin to give a synergistic antibacterial effect against Gram positive and negative bacteria. Nisin and EDTA were encapsulated in nonionic surfactant vesicles or niosomes. Sorbitan monooleate and polyethylene glycol were precursors in preparation of niosomes. Size reduction of niosomes was conducted via extrusion through polycarbonate membrane with pore size of 200 nm. Diameters of prepared blank niosomes and nisin-EDTA-encapsulated niosomes were approximately 130 nm and 270 nm, respectively. Bilayer structure of niosomes was observed from negative staining-transmission electron microscopic images. Long-termed investigation of antimicrobial activity of nisin-EDTA-encapsulated niosomes and free nisin/EDTA were conducted against Staphylococcus aureus and Escherichia coli. Bacterial counts denoted a slow release of nisin-EDTA-encapsulated niosomes overtime whilst free nisin/EDTA gave a sudden bactericidal activity. Due to that free nisin/EDTA was immediately exploited at the beginning, bacterial counts then tended towards higher during the latter time of antimicrobial activity test. Keywords: antibacterial; EDTA; Escherichia coli; niosomes; nisin; Staphylococcus aureus. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.9407 J. Sci. Res. 4 (2), 457-465 (2012)